Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1945-1474.2009.00027.x
|View full text |Cite
|
Sign up to set email alerts
|

A Rural Hospital Takes on Lean

Abstract: The Federal government has initiated an executive order to address quality measurements and incentives promoting quality and efficiency. Healthcare organizations are using Toyota Production System's Lean continuous quality improvement to provide a framework for this. Though large healthcare organizations have the resources to embrace Lean, few rural hospitals have been known to use Lean's process improvement philosophy. This paper discusses the journey a 99-bed rural hospital took to integrate Lean into its or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…(), nurses were dissatisfied with their job when they left nursing tasks undone. Nurses are spending less time in direct patient care and more time troubleshooting problems and completing administrative work (Snyder & McDermott ). Moreover, more than a tenth of working hours is spent in activities such as travel (White et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(), nurses were dissatisfied with their job when they left nursing tasks undone. Nurses are spending less time in direct patient care and more time troubleshooting problems and completing administrative work (Snyder & McDermott ). Moreover, more than a tenth of working hours is spent in activities such as travel (White et al .…”
Section: Discussionmentioning
confidence: 99%
“…Finnish RNs also stated that they did not have time to perform nursing activities in their daily practice on account of non-nursing and administrative tasks (Hinno et al 2012), and according to Bekker et al (2015), nurses were dissatisfied with their job when they left nursing tasks undone. Nurses are spending less time in direct patient care and more time troubleshooting problems and completing administrative work (Snyder & McDermott 2009). Moreover, more than a tenth of working hours is spent in activities such as travel (White et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Health care experts predict that it will take years to truly transform the US health care system and to "hardwire" Lean throughout hospitals. 25 By 2019, the Affordable Care Act is expected to add approximately 32 million Americans to the health insurance rolls. 57 Hospitals are already experiencing many new pressures on their operating margins in response to changes in payment rates to providers, especially under Medicare, and testing of experimental models with bundled payments.…”
Section: Implications For Nursing Educationmentioning
confidence: 99%
“…On the other hand, looking from the perspective of the transformational leadership characteristics, charisma is the top characteristics portrayed by leaders in healthcare. Eight articles reported that the leaders were having and utilizing this trait to initiate and manage the implementation of lean healthcare in their organizations (Snyder & McDermott, 2009 The ability of a leader to inspire employee towards organisational excellence and crafted strategy that suits company's vision is the example of charisma characteristics displayed by leaders in healthcare.…”
Section: Fig 1 Flow Diagram Of the Included Studiesmentioning
confidence: 99%